KOMODIFIKASI FANDOM BLACKPINK DI INDONESIA - Tuty Mutiah, Mutiah; Adityo Fajar; Ilham Albar Pane; Chepi Nurdiansyah; A Rafiq (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2023)
Fandom is a term used to describe activities that reflect the closeness between fans and their idols based on a particular cultural product. Advances in digital technology have made interaction between fandoms and their idols easier, enabling them to consume a variety of products issued by such idols. Unfortunately, fandom activity on digital media is often exploited in the form of collecting user data that is then exploited for commercial purposes. Sometimes, digital media consumption can even become a